Hubungan Status Gizi Dengan Kejadian Anemia Pada Remaja Putri Di Pondok Pesantren La Tansa 2 Tahun 2022 - Anis Ervina; Devi Aulia Rusli; Mila Lestari (Jurnal Obstretika Scientia, 2023)
Adolescents are a group that is divided into two, namely early adolescents and late adolescents. Early adolescence starts from 10-14 years old and late adolescence is 15-19 years old. Adolescence can also be called the period of entering adulthood. Adolescence is inseparable from nutritional problems, namely chronic energy deficiency (CED), obesity and anemia. Anemia is a condition where the number of red blood cells is less than normal and the oxygen capacity in the body is insufficient. The method in this study is correlational analytic with cross sectional design. The population in this study were adolescent girls at the La Tansa 2 Islamic Boarding School. The total sample size was 7 out of 42 population and the sample was taken from the entire population of 42 people. The results of the study found that as many as 99.9% of students who were well-nourished did not experience anemia, as many as 100% of undernourished students experienced anemia. Suggestions for adolescents are expected to make efforts to increase knowledge about good nutrition to prevent anemia by increasing knowledge about balanced nutrition and anemia.